Deformable multi-level feature network applied to nucleus segmentation - Chang, Shulei; Yang, Tingting; Yin, Bowen; Zhang, Jiayi; Ma, Liang; Ding, Yanhui; Sui, Xiaodan (Frontiers in Microbiology, 2024)
IntroductionThe nucleus plays a crucial role in medical diagnosis, and accurate nucleus segmentation is essential for disease assessment. However, existing methods have limitations in handling the diversity of nuclei and differences in staining conditions, restricting their practical application.MethodsA novel deformable multi-level feature network (DMFNet) is proposed for nucleus segmentation. This network is based on convolutional neural network and divides feature processing and mask generation into two levels. At the feature level, deformable convolution is used to enhance feature extraction ability, and multi-scale features are integrated through a balanced feature pyramid. At the mask level, a one-stage framework is adopted to directly perform instance segmentation based on location.ResultsExperimental results on the MoNuSeg 2018 dataset show that the mean average precision (mAP) and mean average recall (mAR) of DMFNet reach 37.8% and 47.4% respectively, outperforming many current advanced methods. Ablation experiments verified the effectiveness of each module of the network.DiscussionDMFNet provides an effective solution for nucleus segmentation and has important application value in medical image analysis.